Conservative methotrexate treatment of a scar pregnancy case: adding evidence to the evidence. - Ligorio, Claudia; Indraccolo, Ugo; Morano, Danila; Greco, Pantaleo (Acta Biomedica Atenei Parmensis, 2021)
A single case of ultrasonographic-guided local injection of methotrexate for managing scar pregnancy is reported. The outcome was successful and had no side effects. The case was reported to increase the evidence supporting this type of management.